Improved non-linear devices for quantum applications - Gil López, Jano; Santandrea, Matteo; Roland, Ganaël; Brecht, Benjamin; Eigner, Christof; Ricken, Raimund; Quiring, Viktor; Silberhorn, Christine (New Journal of Physics)

Universal compressive tomography in the time-frequency domain - Gil López, Jano; Teo, Yong Siah; De, Syamsundar; Brecht, Benjamin; Jeong, Hyunseok; Silberhorn, Christine; Sánchez-Soto, Luis L. (Optica)

Quantum optical coherence: From linear to nonlinear interferometers - Luo, Kai Hong; Santandrea, Matteo; Stefszky, Michael; Sperling, Jan; Massaro, Marcello; Ferreri, Alessandro; Sharapova, Polina; Herrmann, Harald; Silberhorn, Christine (Physical Review A)

Probing the topological Anderson transition with quantum walks - Bagrets, Dmitry; Kim, Kun Woo; Barkhofen, Sonja; De, Syamsundar; Sperling, Jan; Silberhorn, Christine; Altland, Alexander; Micklitz, Tobias (Physical Review Research)

Transient subdiffusion via disordered quantum walks - Geraldi, Andrea; De, Syamsundar; Laneve, Alessandro; Barkhofen, Sonja; Sperling, Jan; Mataloni, Paolo; Silberhorn, Christine (Physical Review Research)

Statistical Benchmarking of Scalable Photonic Quantum Systems - Tiedau, J.; Engelkemeier, M.; Brecht, Benjamin; Sperling, Jan; Silberhorn, Christine (Physical Review Letters)

Experimental entanglement characterization of two-rebit states - Prasannan, Nidhin; De, Syamsundar; Barkhofen, Sonja; Brecht, Benjamin; Silberhorn, Christine; Sperling, Jan (Physical Review A)

Generating two-mode squeezing with multimode measurement-induced nonlinearity - Riabinin, Matvei; Sharapova, Polina; Bartley, Tim; Meier, Torsten (Journal of Physics Communications)

Non-Invasive Visualization of Ferroelectric Domain Structures on the Non-Polar y-Surface of KTiOPO4 via Raman Imaging - Brockmeier, Julian; Mackwitz, Peter Walter Martin; Rüsing, Michael; Eigner, Christof; Padberg, Laura; Santandrea, Matteo; Silberhorn, Christine; Zrenner, Artur; Berth, Gerhard (Crystals)
Potassium titanyl phosphate (KTP) is a nonlinear optical material with applications in high-power frequency conversion or quasi-phase matching in submicron period domain grids. A prerequisite for these applications is a precise control and understanding of the poling mechanisms to enable the fabrication of high-grade domain grids. In contrast to the widely used material lithium niobate, the domain growth in KTP is less studied, because many standard methods, such as selective etching or polarization microscopy, provides less insight or are not applicable on non-polar surfaces, respectively. In this work, we present results of confocal Raman-spectroscopy of the ferroelectric domain structure in KTP. This analytical method allows for the visualization of domain grids of the non-polar KTP y-face and therefore more insight into the domain-growth and -structure in KTP, which can be used for improved domain fabrication.

Extremely low-energy ARPES of quantum well states in cubic-GaN/AlN and GaAs/AlGaAs heterostructures - Hajlaoui, Mahdi; Ponzoni, Stefano; Deppe, Michael; Henksmeier, Tobias; As, Donat Josef; Reuter, Dirk; Zentgraf, Thomas; Springholz, Gunther; Schneider, Claus Michael; Cramm, Stefan; Cinchetti, Mirko (Scientific Reports)
Abstract Quantum well (QW) heterostructures have been extensively used for the realization of a wide range of optical and electronic devices. Exploiting their potential for further improvement and development requires a fundamental understanding of their electronic structure. So far, the most commonly used experimental techniques for this purpose have been all-optical spectroscopy methods that, however, are generally averaging in momentum space. Additional information can be gained by angle-resolved photoelectron spectroscopy (ARPES), which measures the electronic structure with momentum resolution. Here we report on the use of extremely low-energy ARPES (photon energy ~ 7 eV) to increase depth sensitivity and access buried QW states, located at 3 nm and 6 nm below the surface of cubic-GaN/AlN and GaAs/AlGaAs heterostructures, respectively. We find that the QW states in cubic-GaN/AlN can indeed be observed, but not their energy dispersion, because of the high surface roughness. The GaAs/AlGaAs QW states, on the other hand, are buried too deep to be detected by extremely low-energy ARPES. Since the sample surface is much flatter, the ARPES spectra of the GaAs/AlGaAs show distinct features in momentum space, which can be reconducted to the band structure of the topmost surface layer of the QW structure. Our results provide important information about the samples’ properties required to perform extremely low-energy ARPES experiments on electronic states buried in semiconductor heterostructures.

Interferometric method for determining the losses of spatially multi-mode nonlinear waveguides based on second harmonic generation - Santandrea, Matteo; Stefszky, Michael; Roeland, Ganaël; Silberhorn, Christine (Optics Express)

All-dielectric silicon metalens for two-dimensional particle manipulation in optical tweezers - Chantakit, Teanchai; Schlickriede, Christian; Sain, Basudeb; Meyer, Fabian; Weiss, Thomas; Chattham, Nattaporn; Zentgraf, Thomas (Photonics Research)

A dielectric metasurface optical chip for the generation of cold atoms - Zhu, Lingxiao; Liu, Xuan; Sain, Basudeb; Wang, Mengyao; Schlickriede, Christian; Tang, Yutao; Deng, Junhong; Li, Kingfai; Yang, Jun; Holynski, Michael; Zhang, Shuang; Zentgraf, Thomas; et al. (Science Advances)
Compact and robust cold atom sources are increasingly important for quantum research, especially for transferring cutting-edge quantum science into practical applications. In this study, we report on a novel scheme that uses a metasurface optical chip to replace the conventional bulky optical elements used to produce a cold atomic ensemble with a single incident laser beam, which is split by the metasurface into multiple beams of the desired polarization states. Atom numbers ~10 7 and temperatures (about 35 μK) of relevance to quantum sensing are achieved in a compact and robust fashion. Our work highlights the substantial progress toward fully integrated cold atom quantum devices by exploiting metasurface optical chips, which may have great potential in quantum sensing, quantum computing, and other areas.

A photoredox catalysed Heck reaction via hole transfer from a Ru(II)-bis(terpyridine) complex to graphene oxide - Rosenthal, Marta; Lindner, Jörg K N; Gerstmann, Uwe; Meier, Armin; Schmidt, W Gero; Wilhelm, René (Royal Society of Chemistry)

Plasmonic metasurfaces for controlling harmonic generations - Zentgraf, Thomas; Chen, Shumei; Li, Guixin; Zhang, Shuang (Nanoantennas and Plasmonics: Modelling, design and fabrication)

Examination of the evolution of iron oxide nanoparticles in flame spray pyrolysis by tailored in situ particle sampling techniques - Tischendorf, R.; Simmler, M.; Weinberger, C.; Bieber, M.; Reddemann, M.; Fröde, F.; Lindner, J.; Pitsch, H.; Kneer, R.; Tiemann, M.; Nirschl, H.; Schmid, H.-J. (Journal of Aerosol Science)

Influence of lens aberrations, specimen thickness and tilt on differential phase contrast STEM images - Bürger, Julius; Riedl, Thomas; Lindner, Jörg K.N. (Ultramicroscopy)

Waveguide resonator with an integrated phase modulator for second harmonic generation - Stefszky, Michael; Santandrea, Matteo; vom Bruch, Felix; Krapick, S.; Eigner, Christof; Ricken, R.; Quiring, V.; Herrmann, Harald; Silberhorn, Christine (Optics Express)

Metasurfaces help lasers to mode-lock - Sain, Basudeb; Zentgraf, Thomas (Light: Science & Applications)

Polarization-Encrypted Orbital Angular Momentum Multiplexed Metasurface Holography - Zhou, Hongqiang; Sain, Basudeb; Wang, Yongtian; Schlickriede, Christian; Zhao, Ruizhe; Zhang, Xue; Wei, Qunshuo; Li, Xiaowei; Huang, Lingling; Zentgraf, Thomas (ACS Nano)